Drug susceptibility of Brazilian strains of Mycobacterium bovis using traditional and molecular techniques - Patrícia M Parreiras; Francisco CF Lobato; Andréa P Alencar; Telma de Figueiredo; Harrison M Gomes; Neio Boéchat; Andrey P Lage; Ronnie A Assis; Márcia AS Pereira; Patrícia R Souza; Pedro MPC Mota; Philip N Suffys (Memorias do Instituto Oswaldo Cruz, 2004)
Transmission of Mycobacterium bovis from cattle to humans has been reported and can cause tuberculosis (Tb) and a problem in certain risk populations. Therefore, knowledge of resistance of M. bovis towards antibiotics used for therapy of human Tb could help avoiding cure delay and treatment cost increase when dealing with drug resistant organisms. We therefore evaluated the susceptibility of M. bovis isolates towards streptomycin, isoniazide, rifampicin, ethambutol, and ethionamide, the first line antibiotics for human Tb. Therefore, 185 clinical samples from cattle with clinical signs of tuberculosis were processed and submitted to culturing and bacterial isolates to identification and drug susceptibility testing using the proportion method. Among 89 mycobacterial strains, 65 were identified as M. bovis and none were resistant to any of the antibiotics used. Confirmation of present results by future studies, enrolling a large number of isolates and designed to properly represent Brazilian regions, may favor the idea of using isoniazide preventive therapy as part of a Tb control strategy in special situations. Also, nucleic acids from bacterial isolates were submitted to rifoligotyping, a recently described reverse hybridization assay for detection of mutations causing resistance towards rifampicin. Concordance between the conventional and the molecular test was 100%, demonstrating the use of such methodology for rapid evaluation of drug susceptibility in M. bovis.